Application Of Total Quality Management (Tqm), Performance Measurement System And Effectiveness Systems On Managerial Performance: Application Of Total Quality Management (Tqm), Performance Measurement System And Effectiveness Systems On Managerial Performance - Tita Boedi Astuti; Muhamad Rifa’i (Institute of Computer Science (IOCS), 2020)
The application of high TQM will improve managerial performance, and vice versa. Managers will be more motivated to improve performance, if high performance measurements in the form of information needed that provide feedback for improvement and learning. After TQM is applied, managerial performance must be measured to find out how the manager's abilities (keep in mind that this has entered the millennial era) in supporting the company's strategy. The measuring instrument used to determine how much the manager's ability is a performance measurement system based on multicultural, because the performance measurement system based on multicultural is a combination of financial performance and non-financial performance. The multicultural performance measurement system is the Balance Scorecard (BSC). BSC was chosen because the BSC indicator which consists of financial, customer, internal business processes, and learning and growth perspectives and is very comprehensive. These indicators are very applicable to measure the manager's performance. The awards received by middle managers can be in the form of financial and non-financial rewards. Financial awards are external awards given to the performance given to companies in the form of salaries, wages, bonuses, commissions, pensions, accident insurance, and others. While non-financial rewards are part of the work itself such as task completion, achievement, personal development and so on. Performance-based reward systems encourage employees to change their tendencies from enthusiasm to fulfill their own interests to the spirit of meeting organizational interests. Performance-based rewards provide two benefits, namely motivating and providing information (Mulyadi and Jhony, 1998).